RANCANG BANGUN APLIKASI PENJUALAN DAN JASA SERVICE PADA SHOWROOM EXPO YAMAHA MOTOR DI KOTA PERDAGANGAN KABUPATEN SIMALUNGUN - Ilham Alfaridzi; Dedi Suhendro; Iqbal Sanjaya (Jurnal Informatika, 2019)
Motorbikes are motorized vehicles that have two wheels. in a straight line lined up so that when the conditions go at high speed it remains stable because of the gyroscopic force. Moving at high speeds continues to run stable and at low speeds stability always depends on the settings. In Indonesia motorbike users are very popular because they are cheap, easy to reach, save fuel and the maintenance costs are not large. One of the most famous motorbikes in Indonesia is Yamaha with its founder from Japan named Yama Tarakusu. Yamaha motorbike is a service for consumers in providing motorized vehicle maintenance because it is designed by reliable experts. Yamaha Motor Trade Expo Showroom Simalungun Regency dealers selling motorcycles, spare parts while providing service services for consumer motorcycle vehicles have not been maximized and have not been satisfactory because they are still done manually on sales, especially in selling spare parts because there is no fast and accurate information regarding stock or inventory. In terms of service services, there is also no application system running at the Yamaha Motor Trade Expo Showroom in Simalungun Regency. The design of sales and service applications aims to facilitate and accelerate the sales data processing and motorcycle service, so that the administration of sales and information is faster and more accurate. Departing from this, the author designed the application of sales and service services at the Yamaha Motor Trade Expo Showroom in Simalungun Regency in the hope that sales applications and service services can provide fast, precise and accurate information.Keywords : Sales, Motorcycle Services, Microsoft Visual Studio 2010, MySQL